If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -10 = -1(9x + 18) Reorder the terms: -10 + 4x = -1(9x + 18) Reorder the terms: -10 + 4x = -1(18 + 9x) -10 + 4x = (18 * -1 + 9x * -1) -10 + 4x = (-18 + -9x) Solving -10 + 4x = -18 + -9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9x' to each side of the equation. -10 + 4x + 9x = -18 + -9x + 9x Combine like terms: 4x + 9x = 13x -10 + 13x = -18 + -9x + 9x Combine like terms: -9x + 9x = 0 -10 + 13x = -18 + 0 -10 + 13x = -18 Add '10' to each side of the equation. -10 + 10 + 13x = -18 + 10 Combine like terms: -10 + 10 = 0 0 + 13x = -18 + 10 13x = -18 + 10 Combine like terms: -18 + 10 = -8 13x = -8 Divide each side by '13'. x = -0.6153846154 Simplifying x = -0.6153846154
| 4x^2+36y^2-72y-108=0 | | 17-10x=5x+65 | | 2x(x+3)=9 | | y^3-4y^2=0 | | 3(-2-x)=18 | | 7/8*6/5 | | 9m+24= | | 1/2w+7=2w-2 | | 27x-4=9x+2 | | x(x)-5+2forx=6 | | 2-4r=-14 | | 64x^3-49x=0 | | 2n=2n-1 | | 3t+2+2t=-53 | | x(x)-5+12= | | 5x^3+3x^2=125x+75 | | 8/11-2x=-2x+6/11 | | 5x^3/4+2=42 | | 29-5g+3=-3g+6g | | y+2=10 | | 32x-1/5=4 | | 3x-1/5=20 | | .2n-.594=3.5n+9.0 | | -.389y-.974=6.789y | | -3(2x-3)+15=9 | | 5(2x-6)=3(x+4) | | 15-(3m+7)=5+4m-18 | | 2x^2-10=20 | | 8y-6=7y+3 | | x/5+3=5 | | x/5-3=5 | | 6x+5x+15=180 |